Metodologias ativas: um novo (?) método (?) de ensinar (?) - Sampaio, Carlos Magno (2020)
This dissertation is the result of theoretical research, whose objective was to discuss whether the epistemological foundations of Active Learning provide conditions for building knowledge in the teaching and learning process. As educational policies defend their implementation in pedagogical processes and give them a prominent and innovative position, they are designed and applied in a technical way and have not produced many significant results for learning, which led to the hypothesis that they have no epistemological basis in However, using the categories of historical-cultural theory, the desired and necessary active processes in situations of knowledge production and teaching and learning can become mediators of education. Thus, it was proposed to describe and analyze the content of the Active Learning proposal and evaluate its pedagogical effectiveness and, for this purpose, specifically aiming to map, identify and characterize its use, the methodological procedure adopted was the literature review and specialized reading of bibliography on the topic, present in theses, dissertations and articles in databases and repositories. The result of the investigation was the recording of the constitution of the active learning movement, exposing its inspiring and original sources, its theoretical assumptions and the mercantilist tendency that it incorporates. It also advances some theoretical subsidies considered to assess whether the learning was active and to guide the didactic pedagogical process of learning.